Photocatalytic Degradation of Tetracycline by a Novel (CMC)/MIL-101(Fe)/β-CDP Composite Hydrogel - Zhang, Hui; Zhou, Liang; Li, Jing; Rong, Sijia; Jiang, Jianping; Liu, Shengquan (Frontiers in Chemistry, 2021)
Herein, we report a novel carboxymethylcellulose (CMC)/MIL-100(Fe)/β-CDP hydrogel with high photocatalytic activity. β-CDP can significantly enhance the photoactivity of MIL-101(Fe) in the hydrogel prepared by a simple solvothermal method. The structure and property of this composite hydrogel were characterized by Fourier transform infrared spectroscopy, X-ray diffraction, scanning electron microscopy, and transmission electron microscopy. Tetracycline was selected as a model pharmaceutical antibiotic to evaluate the photocatalytic activity of the composite hydrogel under visible light irradiation and darkness, respectively. This composite hydrogel shows excellent activity for degrading pharmaceutical antibiotics under visible light irradiation. The increased photocatalytic activity can be attributed to β-CDP, which acts as a promoter and affords an efficient separation of photogenerated electron-hole pairs of MIL-101(Fe). Moreover, the composite hydrogel is shown to have good water retainability. The hydrogel is inexpensive and shows high photocatalytic activity. Hence, it can be used as an efficient photocatalytic material.